Pembentukan Desa Safety Farming Di Desa Pudak - Aswin, Budi; Halim, Rd.; Azhary, Muhammad Rifqi; Reskiaddin, La Ode; Wardiah, Rizalia (Prodi Ilmu Kesehatan Masyarakat, FKIK Universitas Jambi, 2025)
This community service program aims to establish a Safety Farming Village in Pudak Village, Kumpeh Ulu District, Muaro Jambi Regency, as an effort to improve occupational safety and health (K3) for farmers. Through outreach, training and the establishment of Occupational Health Effort Posts (UKK), farmers are expected to be able to apply K3 principles in farming activities, especially in handling pesticides. The results of the program show an increase in farmers' knowledge and awareness about the importance of work safety, as evidenced by a decrease in the incidence of work accidents and an increase in the use of personal protective equipment (PPE). Apart from that, the establishment of work SOPs and rinse storage houses provides safer facilities for farmers. This program also produces First Aid for Accidents (P3K) training which helps farmers deal with work injuries more swiftly and effectively. This success was supported by partnerships between educational institutions, village stakeholders and farmers, which significantly increased safety awareness and strengthened the sustainability of safe agricultural practices. This program has not only succeeded in improving the quality of life and productivity of farmers, but has also become a model for other villages in implementing Safety Farming.